Addressing the food crisis in Yemen: The private sector’s key role amid local conflict and global market disruptions from the Russia-Ukraine war - Kurdi, Sikandra; Ecker, Olivier; Glauber, Joseph W.; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
The Yemen conflict, underway since early 2015, has led to an ongoing, unprecedented humanitarian emergency. Food needs far exceed current consumption levels, with 3.5 million pregnant or breastfeeding women and children under age five suffering from acute malnutrition and up to 19 million people affected by food insecurity in 2022. Since February 2022, meanwhile, the Russia-Ukraine war has disrupted global supplies of grains and other key agricultural products and driven global food prices higher. Yemen depends heavily on grain imports to feed a population long teetering on the edge of famine. Maintaining wheat flowing into the country and wheat products reaching consumers through private sector importers, processors, and distributors is a critical puzzle piece for managing food security.